2021
DOI: 10.1007/s10964-021-01478-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Mental Well-Being in Young Carers: The Role of Benefit Finding, Coping, Helplessness, and Caring Tasks

Abstract: Although prior research has shown that young carers may perceive benefits from their challenging situation, it is unclear how and when benefit finding leads to better mental health. This study examines pathways through which benefit finding may influence mental well-being. Self-reported data were obtained from 601 adolescents aged 15–21 (Mage = 17.87, 71.9% female) who provided care for a close person with physical or mental health problems. Benefit finding was associated with better mental well-being directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…Subjective well-being, including good mental health, also considerably improved in the intervention group as earlier studies suggested [ 35 , 36 ]. Subjective well-being may gradually grow through the experience of benefit finding since benefit finding is closely related to better adaptation and sense making.…”
Section: Discussionsupporting
confidence: 75%
“…Subjective well-being, including good mental health, also considerably improved in the intervention group as earlier studies suggested [ 35 , 36 ]. Subjective well-being may gradually grow through the experience of benefit finding since benefit finding is closely related to better adaptation and sense making.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies have investigated the consequences of being a YC. They showed that assuming such a role can have positive and negative consequences on a physical, psychological, social or educational level [ 3 , 4 , 5 , 6 , 7 , 8 ]. Specifically, regarding education, some youths experience academic difficulties, including problems concentrating in class, failure to complete homework, absenteeism, discrimination, and school dropout [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that the benefit finding of caregivers was a mediating variable of caregiver burden and caregiver mental health. Family caregivers of multiple cancer patients reported ( 49 , 50 ) changes in individual cognitive behaviors in response to negative events while accompanying cancer patients during treatment: appreciation and acceptance of life, improved interpersonal relationships, spiritual growth, and improved health behaviors. Benefit finding as a cognitive-behavioral process for individuals to cope with stress and negative events can help individuals to re-build positive coping mechanisms ( 14 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%